2010
DOI: 10.1007/s12263-010-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in human peripheral blood mononuclear cells as biomarkers for nutritional in vitro and in vivo investigations

Abstract: Identification of chemopreventive substances may be achieved by measuring biological endpoints in human cells in vitro. Since generally only tumour cells are available for such investigations, our aim was to test the applicability of peripheral blood mononuclear cells (PBMC) as an in vitro primary cell model since they mimic the human in vivo situation and are relatively easily available. Cell culture conditions were refined, and the basal variation of gene expression related to drug metabolism and stress resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…With regard to nutrition, although this is a less explored field, PBMC in vitro systems constitute a rapid and low‐cost profiling method to explore the potential beneficial effects of food ingredients on metabolism and health. In fact, it has been demostrated that food compounds modulate gene expression in ex vivo human PBMC and, thus, ex vivo systems have been proposed as a suitable approach in the search of nutrigenomics biomarkers (Hofmann et al., ). One of the most studied fields is the anti‐inflammatory effect of different food bioactive components (Bouwens, Grootte Bromhaar, Jansen, Müller, & Afman, ; Myhrstad et al., ).…”
Section: Pbc In Vitro Studies For Nutrition Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to nutrition, although this is a less explored field, PBMC in vitro systems constitute a rapid and low‐cost profiling method to explore the potential beneficial effects of food ingredients on metabolism and health. In fact, it has been demostrated that food compounds modulate gene expression in ex vivo human PBMC and, thus, ex vivo systems have been proposed as a suitable approach in the search of nutrigenomics biomarkers (Hofmann et al., ). One of the most studied fields is the anti‐inflammatory effect of different food bioactive components (Bouwens, Grootte Bromhaar, Jansen, Müller, & Afman, ; Myhrstad et al., ).…”
Section: Pbc In Vitro Studies For Nutrition Researchmentioning
confidence: 99%
“…Moreover, the PBMC ex vivo approach may be helpful to validate the use of PBMC as a surrogate tissue in other contexts rather than inflammation; for example, Hoffman et al. demonstrated using human PBMC as a primary cell model to demonstrate that these blood cells could be a suitable surrogate tissue to study the status of cellular detoxification systems and the potential modulation by food ingredients (Hofmann et al., ).…”
Section: Pbc In Vitro Studies For Nutrition Researchmentioning
confidence: 99%
“…PBMCs were counted using a Z2 cell and particle counter (Beckman Coulter Nederland B.V., Woerden, Utrecht, The Netherlands) and 2 × 10 6 cells per well were transferred to a 24 well plate in a total volume of 1 mL per well. As a model for direct interaction of cellulose with immune cells (Hofmann et al, 2010;van Hemert et al, 2010;Vogt et al, 2013), PBMCs were incubated for 24 h (37°C and 5% CO 2) with a thoroughly homogenised suspension of 1 or 100 µg/mL of cellulose (Sigma-Aldrich Chemie B.V.), or with normal culture medium, or with 2 ng/mL LPS (Escherichia coli serotype 0111:B4; SigmaAldrich Chemie B.V.).…”
Section: Human Peripheral Blood Mononuclear Cell Isolation Culture mentioning
confidence: 99%
“…PBMCs may be also adversely affected by cryopreservation. 731 Juge et al 673 in their comprehensive review of SFN in cancer refer to a similar glutathione-related counter-intuitive finding in that glutathione reductase (GSR) needed for the regeneration of glutathione was consistently inhibited by SFN in several cell culture lines. 732 Nevertheless, this study showed that the intervention resulted in increased plasma GSH conjugates, the presence of which is dependent on the action of enzymes of the glutathione-S-transferase family of which GSTP1 is one member.…”
Section: Redox-related Effectsmentioning
confidence: 96%
“…731 The nature of microarray studies is that they query large gene datasets but lack the accuracy of platforms such as RT-qPCR. In a next step, it would be advantageous to select and investigate a number of the genes of interest from the EASYGENEX Study, using this more sensitive tool.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%